The Use of Hanging Bottle Media in Improving Pencak Silat Front Kick Skills among Seventh-Grade Students - Puji Lestari; Norma Anggara; Syamsul Arifin; Recky Ahmad Haffyandi (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – This study aims to determine the effect of using hanging bottles as a training aid on Pencak Silat front kick skills among seventh-grade students. This research was prompted by students’ low proficiency in performing front kick techniques, as evidenced by incorrect kick direction, poor balance, and suboptimal motor coordination. Methods – This study employed a quantitative approach with a pre-experimental one-group pretest-posttest design. The sample consisted of 26 seventh-grade students. The instrument used was a practical test assessing front kick skills based on movement technique indicators. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, the Wilcoxon Signed-Rank Test, and N-Gain analysis. Findings – The results revealed a significant improvement between pretest and posttest scores, with an asymptotic significance value of p < 0.001. The mean pretest score increased from 43.65 to 86.15 on the posttest. Furthermore, the average N-Gain value of 0.76 (76.47%) fell into the